Mapping the social representations of Psychology: a study in a Portuguese context - Sónia P. Gonçalves; C. Nogueira; Marlene Vale da Silva; Mary Sandra Carlotto (2023)
Abstract Objective: The present study aimed to analyse the social representations of Psychology in a sample of Portuguese respondents, thus contributing to a better understanding of the social meaning of this scientific area. Method: A free association task was performed by a sample of 205 Portuguese individuals who were given the word “Psychology” as a stimulus. Data were analysed using content analysis, supported by the Max-Qda software. Results: The main results show a greater diversity of representations compared to previous studies. However, the dominant representation in terms of intervention is still the curative clinic and the medical paradigm. Conclusion: This research made it possible to highlight the need for Psychology professionals, and the entities that represent them, to reinforce the visibility and awareness of the community in general, of the application areas both in the scientific and professional context.